Monitoring the Urban Heat Island Phenomenon in Pontianak City, West Kalimantan, using Google Earth Engine - Sari, Kartika; Sanjaya, Hartanto; Muhardi, Muhardi (POSITRON, 2024)
The urban heat island (UHI) phenomenon can cause the land surface temperature (LST) in the city center to be higher than in the surrounding area. The population of Pontianak City increases yearly, resulting in land cover changes and LST distribution. This research aims to monitor the UHI phenomenon by identifying the temporal distribution of LST in Pontianak City. This research analyses the Landsat 8 thermal band, which is converted into LST value based on the normalised difference vegetation index (NDVI). The land cover classification was conducted using a random forest algorithm and acquisition of confusion matrix classification accuracy value. This research utilizes the Google Earth Engine (GEE) platform because of its ability to process satellite data continuously and has data with a sizeable spatiotemporal dimension. The results show a strong relationship between urban development and LST distribution. Based on the land cover classification in 2014 and 2019, there is a significant change in the composition of the surface, namely, built-up land has increased, while open space and vegetation land have decreased. Time series analysis also shows that the average LST of built-up land, open space, and vegetation are 28.10℃, 22.80℃, and 21.56℃, respectively. The results of monitoring the UHI phenomenon can help in better urban spatial planning, especially in increasing green space, because it is proven effective in reducing land surface temperature.